2016
DOI: 10.1080/09273948.2016.1236972
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Patterns and Causes of Intraocular Inflammation in a Uveitis Patient Cohort from Egypt

Abstract: In this uveitis patient population from Egypt, panuveitis was the most commonly encountered anatomic diagnosis. Behçet disease was the most common identified cause of uveitis followed by VKH disease. Herpes-related uveitides and parasitic granulomas represented the most evident causes of infectious uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Similar cluster was reported from different geographical locations along the basin of river Nile by R.M. Amin et al from Egypt with granulomatous anterior uveitis after swimming in the river [8][9] . Here again the etiological agent was proven by molecular diagnostics to be trematode.…”
Section: Epidemiologysupporting
confidence: 87%
“…Similar cluster was reported from different geographical locations along the basin of river Nile by R.M. Amin et al from Egypt with granulomatous anterior uveitis after swimming in the river [8][9] . Here again the etiological agent was proven by molecular diagnostics to be trematode.…”
Section: Epidemiologysupporting
confidence: 87%
“…In a recent epidemiological study, a preponderance of cases of paediatric parasitic AC granulomas from Egypt was reported (34.8% of paediatric uveitis cases in the study population) 19. The present work was conducted to provide characterisation of this unique pathology in Egypt and to further describe the clinical patterns of those waterborne infections that affect the human eye.…”
Section: Discussionmentioning
confidence: 93%
“…Presumed trematode-induced uveitis is a newly recognized cause of intraocular granulomatous inflammation in children usually presenting with single or multiple pearl-like white nodules in the anterior chamber (AC) with or without subconjunctival lesions or corneal opacities [1][2][3][4]. Intermediate uveitis with snowbanking and posterior uveitis can also be found [5].…”
Section: Introductionmentioning
confidence: 99%